Positive electrode material and preparation method thereof, positive electrode plate and battery

By covering the nanoscale SiO2 and TiO2 layers on the surface of lithium manganese iron phosphate particles, the problem of insufficient conductivity and cyclic performance of the material is solved, and the electrochemical performance and cycle life of the lithium-ion battery are significantly improved.

CN119447228AActive Publication Date: 2025-02-14EVE POWER CO LTD

Patent Information

Application Number
CN202411481074.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-14
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

As the positive electrode material of lithium ion batteries, lithium manganese iron phosphate has poor conductivity, rate performance and cycle performance, resulting in unsatisfactory electrochemical performance and cycle life of the battery.

Method used

By sequentially coating the nanoscale SiO2 layer and TiO2 layer on the surface of lithium manganese iron phosphate particles, a double-layer shell structure is formed to improve the conductivity and electrochemical properties of the material.

Benefits of technology

This method effectively reduces the contact between lithium manganese iron phosphate particles and electrolyte, reduces the occurrence of side reactions, alleviates the attenuation of the cycle life of the battery, and improves the rate performance and discharge capacity retention rate of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a positive electrode material and a preparation method thereof, a positive electrode plate and a battery, the positive electrode material comprises lithium manganese iron phosphate particles, a first shell layer and a second shell layer, the first shell layer and the second shell layer sequentially coat the surfaces of the lithium manganese iron phosphate particles, the material of the first shell layer comprises nanoscale SiO2 particles, and the material of the second shell layer comprises nanoscale TiO2 particles. The surfaces of the lithium manganese iron phosphate particles are sequentially coated with the SiO2 layer and the TiO2 layer, so that the contact between the lithium manganese iron phosphate particles and an electrolyte can be reduced, the side reaction between the lithium manganese iron phosphate particles and the electrolyte in the electrochemical reaction process is reduced, the cycle life attenuation of the battery is relieved, the dissolution of Mn element is reduced, and the service life of the battery is prolonged. Therefore, the battery impedance increase caused by deposition of Mn < 2 + > on the negative electrode in the circulation process is relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet, and a battery. Background Art

[0002] Lithium manganese iron phosphate (LMFP) is a new type of phosphate lithium-ion battery positive electrode material obtained by doping manganese elements on the basis of lithium iron phosphate. It has the same olivine structure as lithium iron phosphate. It not only retains the same safety performance as lithium iron phosphate, but also has a higher voltage platform, which gives it a higher energy density and better low-temperature performance. Therefore, it has attracted much attention.

[0003] However, lithium manganese iron phosphate currently has problems such as poor conductivity, rate performance and cycle performance. The following three methods are usually used to modify lithium manganese iron phosphate: 1. By coating the surface of LMFP material with conductive carbon materials (such as graphite, amorphous carbon, carbon nanotubes, cracked carbon and other carbon materials), the conductivity and electrochemical performance of LMFP are improved; 2. By introducing a small amount of "dopants" such as cobalt, nickel, vanadium, etc. through doping to improve the electrical properties of LMFP materials; 3. By nano-sizing LMFP materials, the migration path of lithium ions in the primary particles of the material is shortened, thereby improving the charge and discharge performance of the material. After adopting the above three ways and methods, the performance of LMFP materials can be improved, but the electrochemical performance and cycle performance of the materials are still not ideal. Summary of the invention

[0004] The embodiments of the present invention provide a positive electrode material and a preparation method thereof, a positive electrode plate, and a battery, which can improve the technical problems of unsatisfactory electrochemical performance and cycle performance of lithium manganese iron phosphate in the related art.

[0005] In a first aspect, an embodiment of the present invention provides a positive electrode material, comprising lithium iron manganese phosphate particles and a first shell layer and a second shell layer sequentially coated on the surface of the lithium iron manganese phosphate particles, wherein the material of the first shell layer comprises nano-scale SiO 2 Particles, the material of the second shell layer includes nano-sized TiO 2 Particles.

[0006] In one embodiment, the SiO 2 The average particle size of the particles is ≤ 8 nm; and / or,

[0007] The TiO 2 The average particle size of the particles is ≤ 8 nm; and / or,

[0008] The chemical formula of the lithium iron manganese phosphate particles can be LiMn x Fe (1-x) PO 4 , where 0.1≤X≤0.9.

[0009] In one embodiment, in the positive electrode material, the SiO 2 Particles, the TiO 2 The mass percentage of the particles and the lithium iron manganese phosphate particles is (0.3%-0.7%): (0.3%-0.7%): (98.6%-99.4%).

[0010] In a second aspect, an embodiment of the present invention provides a method for preparing a positive electrode material, comprising the following steps:

[0011] Provide nano-SiO 2 particles, lithium manganese iron phosphate particles and an alcohol solvent, the SiO 2 The particles are dispersed in the alcohol solvent, the lithium iron manganese phosphate particles are added, and first heating and stirring are performed to obtain first solid particles;

[0012] The surface of the first solid particle is coated with nano-sized TiO 2 particles to obtain positive electrode materials.

[0013] In one embodiment, in the positive electrode material, the SiO 2 Particles, the TiO 2 The mass percentage of the particles and the lithium manganese iron phosphate particles is (0.3%-0.7%): (0.3%-0.7%): (98.6%-99.4%); and / or,

[0014] The temperature of the first heating is 60° C. to 90° C., and the time of the first heating is 4 h to 12 h.

[0015] In one embodiment, the surface of the first solid particles is coated with nano-sized TiO 2 Particles, including:

[0016] Providing tetra-n-butyl titanate and anhydrous ethanol, dispersing the tetra-n-butyl titanate in the anhydrous ethanol, and mixing the tetra-n-butyl titanate with the first solid particles after dispersion to obtain a suspension;

[0017] Water is provided and added to the suspension, and a second heating and stirring is performed.

[0018] In one embodiment, the second heating temperature is 50° C.-70° C., and the second heating time is 4 h-8 h.

[0019] In one embodiment, providing water and adding it to the suspension comprises:

[0020] An aqueous solution of ethanol is provided and added to the suspension.

[0021] In one embodiment, the volume ratio of ethanol to water in the ethanol aqueous solution is (1-3):1.

[0022] In one embodiment, the invention further comprises: coating the surface of the first solid particles with nano-sized TiO 2 After the particles are formed, they are sintered to obtain the positive electrode material.

[0023] In one embodiment, the sintering temperature is 400° C.-600° C., and the sintering time is 3 h-6 h.

[0024] In a third aspect, an embodiment of the present invention provides a positive electrode plate, comprising the above-mentioned positive electrode material.

[0025] In a fourth aspect, an embodiment of the present invention provides a battery, comprising the above-mentioned positive electrode plate.

[0026] Beneficial effects of the embodiments of the present invention:

[0027] In an embodiment of the present invention, SiO 2 Layer and TiO 2 The layer can reduce the contact between lithium iron manganese phosphate particles and the electrolyte, reduce the occurrence of side reactions between lithium iron manganese phosphate particles and the electrolyte during the electrochemical reaction, thereby alleviating the battery cycle life attenuation, and at the same time reduce the dissolution of Mn elements, thereby alleviating the Mn element during the cycle. 2+ Deposition on the negative electrode causes an increase in battery impedance; TiO 2 It is an electrochemically inactive material and does not participate in the electrochemical reaction. During the Li ion deintercalation process, TiO 2 The lattice can act as a conductor for electrons and ions, allowing Li ions to pass freely through the TiO 2 lattice, thereby improving the rate performance of the battery; SiO 2 It is an electrochemically inactive material with a thin and uniform coating effect, high mechanical properties, and can remain stable after multiple charge and discharge cycles. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention. In the present invention, unless otherwise specified, the directional words used, such as "upper" and "lower", generally refer to the upper and lower parts of the device in actual use or working state; while "inside" and "outside" refer to the outline of the device.

[0029] The technical solution of this application is as follows:

[0030] In a first aspect, an embodiment of the present application provides a positive electrode material, comprising lithium iron manganese phosphate particles and a first shell layer and a second shell layer sequentially coated on the surface of the lithium iron manganese phosphate particles, wherein the material of the first shell layer comprises nano-scale SiO 2 Particles, the material of the second shell layer includes nano-sized TiO 2 Particles.

[0031] In this application, SiO 2 Layer and TiO 2 The layer can reduce the contact between lithium iron manganese phosphate particles and the electrolyte, reduce the occurrence of side reactions between lithium iron manganese phosphate particles and the electrolyte during the electrochemical reaction, thereby alleviating the battery cycle life attenuation, and at the same time reduce the dissolution of Mn elements, thereby alleviating the Mn element during the cycle. 2+ Deposition on the negative electrode causes an increase in battery impedance; TiO 2 It is an electrochemically inactive material and does not participate in the electrochemical reaction. During the Li ion deintercalation process, TiO 2 The lattice can act as a conductor for electrons and ions, allowing Li ions to pass freely through the TiO 2 lattice, thereby improving the rate performance of the battery; SiO 2 It is an electrochemically inactive material with a thin and uniform coating effect, high mechanical properties, and can remain stable after multiple charge and discharge cycles.

[0032] In some embodiments, the SiO 2 The average particle size of the particles is ≤8 nm, for example, 8 nm, 7 nm, 6.5 nm, 6 nm, 5.5 nm, 5 nm, 4.5 nm, 4 nm, 3.5 nm, etc. Within this range, a good coating effect can be achieved on the lithium manganese iron phosphate particles to reduce the occurrence of vacancies.

[0033] In some embodiments, the TiO 2 The average particle size of the particles is ≤8 nm, for example, 8 nm, 7 nm, 6.5 nm, 6 nm, 5.5 nm, 5 nm, 4.5 nm, 4 nm, 3.5 nm, etc. Within this range, a good coating effect can be achieved on the lithium manganese iron phosphate particles to reduce the occurrence of vacancies.

[0034] In some embodiments, TiO 2 The particles are prepared by hydrolysis of tetrabutyl titanate. 2 The average particle size of the particles is ≤8nm.

[0035] In some embodiments, in the positive electrode material, SiO 2 Particles, TiO 2 The mass percentage of particles and lithium manganese iron phosphate particles is (0.3%-0.7%):(0.3%-0.7%):(98.6%-99.4%), for example, it can be 0.7%:0.7%:98.6%, 0.6%:0.6%:98.8%, 0.5%:0.7%:98.8%, 0.7%:0.5%:98.8%, 0.5%: 0.5%:99%, 0.3%:0.7%:99%, 0.7%:0.3%:99%, 0.4%:0.6%:99%, 0.6%:0.4%:99%, 0.4%:0.4%:99.2%, 0.5%:0.3%:99.2%, 0.3%:0.5%:99.2%, 0.3%:0.3%:99.4%, etc. Within this range, the lithium manganese iron phosphate particles can be covered with SiO 2 Particles and TiO 2 The particles are better coated to form a coating layer, and at the same time the thickness of the coating layer can be moderate so that lithium ions can be effectively inserted and deintercalated.

[0036] As an example, the chemical formula of lithium manganese iron phosphate used in this application can be LiMn x Fe (1-x) PO 4 , where 0.1≤X≤0.9.

[0037] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode material, comprising the following steps:

[0038] S1. Provide nano-scale SiO 2 particles, lithium manganese iron phosphate particles and an alcohol solvent, the SiO 2 The particles are dispersed in the alcohol solvent, the lithium iron manganese phosphate particles are added, and first heating and stirring are performed to obtain first solid particles;

[0039] S2, coating the surface of the first solid particles with nano-sized TiO 2 particles to obtain positive electrode materials.

[0040] In step S1,

[0041] In some embodiments, the SiO 2 The particles are dispersed in the alcohol solvent, comprising:

[0042] The SiO 2 The particles are added into the alcohol solvent, stirred, and then subjected to ultrasonic treatment.

[0043] In this application, due to the nano-scale SiO 2The particles are easy to agglomerate. 2 Dispersed in alcohol solvents and subjected to ultrasonic treatment, nano-SiO 2 dispersion, so that the coating of lithium manganese iron phosphate particles is more uniform and the coating effect is improved.

[0044] In some embodiments, the stirring time is 5 min-15 min, for example, it can be 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, etc., and the ultrasonic treatment time is 20 min-40 min, for example, it can be 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, 32 min, 34 min, 36 min, 38 min, 40 min, etc.

[0045] In some embodiments, in the positive electrode material, SiO 2 Particles, TiO 2 The mass percentage of particles and lithium manganese iron phosphate particles is (0.3%-0.7%):(0.3%-0.7%):(98.6%-99.4%), for example, it can be 0.7%:0.7%:98.6%, 0.6%:0.6%:98.8%, 0.5%:0.7%:98.8%, 0.7%:0.5%:98.8%, 0.5%: 0.5%:99%, 0.3%:0.7%:99%, 0.7%:0.3%:99%, 0.4%:0.6%:99%, 0.6%:0.4%:99%, 0.4%:0.4%:99.2%, 0.5%:0.3%:99.2%, 0.3%:0.5%:99.2%, 0.3%:0.3%:99.4%, etc. Within this range, the lithium manganese iron phosphate particles can be covered with SiO 2 Particles and TiO 2 The particles are better coated to form a coating layer, and at the same time the thickness of the coating layer can be moderate so that lithium ions can be effectively inserted and deintercalated.

[0046] As an example, the alcohol solvent includes isopropanol, methanol, ethanol, propanol, butanol, benzyl alcohol, and ethylene glycol. 2 The dispersion effect of particles, and the alcohol solvents are easy to volatilize and can be easily operated, thereby improving the coating effect.

[0047] In some embodiments, the first heating temperature is 60°C to 90°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, etc., and the first heating time is 4h-12h, for example, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc. Within this range, the solvent can be fully evaporated and the nano-SiO 2 The particles are effectively coated on the surface of lithium manganese iron phosphate particles. If the temperature is too low, the solvent cannot be fully evaporated. If the temperature is too high, the solvent evaporates quickly, the surface tension of the solvent decreases, and SiO 2 Agglomeration between particles.

[0048] In step S2,

[0049] In some embodiments, the surface of the first solid particles is coated with nano-sized TiO 2 Particles, including:

[0050] Providing tetra-n-butyl titanate and anhydrous ethanol, dispersing the tetra-n-butyl titanate in the anhydrous ethanol, and mixing the tetra-n-butyl titanate with the first solid particles after dispersion to obtain a suspension;

[0051] Water is provided and added to the suspension, and a second heating and stirring is performed.

[0052] In the embodiment of the present application, tetrabutyl titanate is hydrolyzed to generate TiO 2 By adding the first solid particles into the hydrolysis reaction of tetrabutyl titanate, the TiO 2 Coating the first solid particles can improve the coating effect. Tetrabutyl titanate can coordinate with anhydrous ethanol to form a complex, thereby stabilizing the structure of the tetrabutyl titanate molecule and slowing down the hydrolysis reaction. At the same time, anhydrous ethanol can fully dissolve the tetrabutyl titanate and make it evenly dispersed.

[0053] In some embodiments, dispersing the tetra-n-butyl titanate in the anhydrous ethanol comprises:

[0054] After the tetra-n-butyl titanate and the anhydrous ethanol are mixed, ultrasonic treatment is performed.

[0055] In some embodiments, the ultrasonic treatment time is 20 min-40 min, for example, 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, 32 min, 34 min, 36 min, 68 min, 40 min, etc. Within this range, tetra-n-butyl titanate can be fully dispersed in anhydrous ethanol, and its agglomeration phenomenon can be alleviated.

[0056] In some embodiments, the second heating temperature is 50°C-70°C, for example, 50°C, 52°C, 54°C, 56°C, 58°C, 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, etc. The second heating time is 4h-8h, for example, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 8h, etc. Within this range, ethanol can be fully evaporated and the generated nano-TiO 2 The particles are effectively coated with SiO 2 If the temperature is too low, the ethanol solvent cannot be fully evaporated. If the temperature is too high, the solvent evaporates quickly, and the surface tension of the solvent decreases, which will cause TiO 2 Agglomeration between particles.

[0057] In some embodiments, providing water and adding it to the suspension comprises:

[0058] An aqueous solution of ethanol is provided and added to the suspension.

[0059] In the present application, the ethanol aqueous solution can dilute the water concentration, thereby slowing down the hydrolysis rate of tetrabutyl titanate. At the same time, the ethanol solvent is easy to volatilize and can be easily operated.

[0060] In some embodiments, the volume ratio of ethanol to water in the aqueous solution of ethanol is (1-3):1, for example, 1:1, 1.2:1, 1.4:1, 1.6:1, 1.8:1, 2:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1, 3:1. Within this range, by controlling the volume ratio of ethanol to water, the hydrolysis rate of tetrabutyl titanate can be controlled, so that TiO 2 The particles are coated with SiO 2 The surface distribution of lithium manganese iron phosphate particles is more uniform.

[0061] In some embodiments, the method further comprises: coating the surface of the first solid particles with nano-sized TiO 2 After the particles are formed, they are sintered to obtain the positive electrode material.

[0062] In some embodiments, the method further includes: after the second heating and stirring, sintering to obtain a positive electrode material.

[0063] In some embodiments, the sintering temperature is 400°C-600°C, for example, 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, 520°C, 540°C, 560°C, 580°C, etc. The sintering time is 3h-6h, for example, 3h, 3.5h, 4h, 4.5h, 5.5h, 6h, etc. Within this range, the lithium manganese iron phosphate particles can be melted and regenerated, thereby reacting with SiO 2 and TiO 2 The particles are more firmly bound together, thereby reducing defects on the surface of the lithium manganese iron phosphate particles.

[0064] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising the above-mentioned positive electrode material.

[0065] In a fourth aspect, an embodiment of the present application provides a battery, comprising the above-mentioned positive electrode plate.

[0066] Example 1

[0067] A method for preparing a positive electrode material comprises the following steps:

[0068] (1) SiO with a particle size D50 of 6 nm 2 The particles were added to isopropanol and stirred for 10 min, then ultrasonically treated for 30 min, and then 2 LiMn is added to the particles at a mass ratio of 0.5:99 0.5 Fe 0.5 PO 4 The mixture was stirred at 75°C for 8 hours to obtain first solid particles.

[0069] (2) Tetrabutyl titanate (C 16 H 36 O 4 Ti) was dissolved in anhydrous ethanol and ultrasonically treated for 30 min, and then added to the first solid particles (wherein SiO 2 TiO 2 The mass ratio of the converted amount is 0.5:0.5, that is, SiO 2 The mass ratio of the particles to tetra-n-butyl titanate is 0.5:2.13), and a suspension is obtained by mixing. An ethanol aqueous solution (the volume ratio of ethanol to water is 2:1) is added to the suspension, and then stirred at 60° C. for 6 hours to obtain a second solid particle.

[0070] (3) The second solid powder is added into a muffle furnace and sintered at 500° C. for 4 h in an air atmosphere to obtain a positive electrode material.

[0071] Example 2

[0072] This embodiment is basically the same as Embodiment 1, except that SiO 2 Particles, TiO2 in tetrabutyl titanate 2 The conversion amount of LiMn 0.5 Fe 0.5 PO 4 The mass ratio is 0.3:0.5:99.2.

[0073] Example 3

[0074] This embodiment is basically the same as Embodiment 1, except that SiO 2 Particles, TiO2 in tetrabutyl titanate 2 The conversion amount of LiMn 0.5 Fe 0.5 PO 4 The mass ratio is 0.7:0.5:98.8.

[0075] Example 4

[0076] This embodiment is basically the same as Embodiment 1, except that SiO 2 Particles, TiO2 in tetrabutyl titanate 2 The conversion amount of LiMn 0.5 Fe 0.5 PO 4 The mass ratio is 0.5:0.3:99.2.

[0077] Example 5

[0078] This embodiment is basically the same as Embodiment 1, except that SiO 2 Particles, TiO2 in tetrabutyl titanate 2 The conversion amount of LiMn 0.5 Fe 0.5 PO 4 The mass ratio is 0.5:0.7:98.8.

[0079] Example 6

[0080] This embodiment is basically the same as Embodiment 1, except that SiO 2 Particles, TiO2 in tetrabutyl titanate 2 The conversion amount of LiMn 0.5 Fe 0.5 PO 4 The mass ratio is 1.2:0.5:98.3.

[0081] Example 7

[0082] This embodiment is basically the same as Embodiment 1, except that SiO2 Particles, TiO2 in tetrabutyl titanate 2 The conversion amount of LiMn 0.5 Fe 0.5 PO 4 The mass ratio is 0.5:1.2:98.3.

[0083] Example 8

[0084] This embodiment is basically the same as Embodiment 1, except that the sintering temperature in step (3) of this embodiment is 400°C.

[0085] Example 9

[0086] This embodiment is basically the same as Embodiment 1, except that the sintering temperature in step (3) of this embodiment is 600°C.

[0087] Comparative Example 1

[0088] (1) SiO 2 Particles (particle size D50 is 6nm) and tetrabutyl titanate (C 16 H 36 O 4 Ti) as SiO 2 TiO 2 The mass ratio of the converted amount of was 0.5:0.5, added to anhydrous ethanol, stirred for 10 minutes, and then ultrasonically treated for 30 minutes, and then LiMn was added. 05 Fe 05 PO 4 (SiO 2 Particles and LiMn 0.5 Fe 0.5 PO 4 The mass ratio of the particles is 0.5:99), and then an ethanol aqueous solution (the volume ratio of ethanol to water is 2:1) is added, followed by stirring at 75°C for 8 hours to obtain the first solid particles;

[0089] (2) The second solid powder is added into a muffle furnace and sintered at 500° C. for 4 h in an air atmosphere to obtain a positive electrode material.

[0090] Comparative Example 2

[0091] This comparative example is basically the same as Example 1, except that step (2) is not performed in this comparative example, and SiO 2 The mass is similar to that of SiO in Example 1. 2 Quality and TiO 2 The amount generated is the same.

[0092] Comparative Example 3

[0093] This comparative example is basically the same as Example 1, except that step (1) is not performed in this comparative example. 0.5 Fe 0.5 PO 4 Directly add it into anhydrous ethanol dissolved with tetrabutyl titanate, and the generated TiO 2 The mass is similar to that of SiO in Example 1. 2 Quality and TiO 2 The amount generated is the same.

[0094] Test example:

[0095] The positive electrode materials obtained in the examples and comparative examples and the uncoated LiMn 0.5 Fe 0.5 PO 4 As the positive electrode active material, graphite is used as the negative electrode active material, and the diaphragm is used as the PE diaphragm. The positive electrode, diaphragm, and negative electrode are stacked in order, and the battery core is obtained by the stacking process. The battery core is placed in an outer packaging shell, dried, and the electrolyte (1.2mol / L LiPF 6 A solution dissolved in a 3:7 mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) is obtained through vacuum packaging, standing, formation, and capacity separation processes to obtain a lithium-ion battery.

[0096] The obtained lithium-ion battery was subjected to a discharge HPPC test: the battery was charged at 4.25V and 1 / 3C constant current and constant voltage, and after the cut-off current was 0.05C, it was discharged at 1 / 3C constant current, and the cut-off capacities were 0.3C, 0.5C, and 0.7C respectively. Then, 1C was used for 30s to calculate the discharge HPPC of 30%, 50%, and 70% SOC using the following formula: R = (V 2 -V 1 ) / 1C, where V 2 The voltage after 1C discharge for 30s, V 1 It is the voltage after 1C discharge for 30s, 1C=1Q, Q is the nominal capacity of the battery.

[0097] The obtained lithium-ion battery was tested for discharge capacity retention rate: the battery was charged at 4.25V and 1 / 3C constant current and constant voltage, and after being fully charged with a cut-off current of 0.05C, it was discharged with a constant current of 1C, 2C, and 3C, and a cut-off voltage of 2.5V.

[0098] The obtained lithium-ion battery was subjected to cycle performance test and Mn element dissolution test: the battery was charged at 4.25V and 1C constant current and voltage, fully charged at a cut-off current of 0.05C, and then discharged to 2.5V at 1C constant current, and the charge and discharge cycle was 500 cycles. Then, the negative electrode sheet obtained by disassembling the empty battery (empty battery refers to a battery with 0% SOC, and the power is 0) was soaked in DMC for 5 hours, dried, and then scraped for ICP test of negative electrode Mn element dissolution.

[0099] The test data is shown in Table 1.

[0100] Table 1

[0101]

[0102] From Table 1, we can see that:

[0103] Compared with Examples 1 to 5, the battery discharge capacity retention rate and cycle performance of Example 1 are higher, which shows that SiO 2 Dosage and TiO 2 The amount generated affects the discharge capacity retention and cycle performance of the battery.

[0104] Compared with Example 6, the internal resistance of the batteries of Examples 1-5 is smaller, the Mn element is less dissolved, and the discharge capacity retention rate is higher. 2 Compared with Examples 8 and 9, the battery of Example 1 has a smaller internal resistance, less Mn element dissolution, higher discharge capacity retention rate and cycle performance, which shows that the sintering temperature affects the performance of the battery.

[0105] Compared with Comparative Example 1, the battery of the embodiment has a smaller internal resistance, less Mn element dissolution, higher discharge capacity retention rate and cycle performance. The reason is that the positive electrode material of the battery of the embodiment is coated with SiO 2 Particles, TiO 2 The surface of the positive electrode material lithium manganese iron phosphate particles of the battery of comparative example 1 is mixed with SiO 2 Particles, TiO 2 Particles.

[0106] Compared with Comparative Example 2, the battery of the embodiment has a smaller internal resistance, a higher discharge capacity retention rate and a higher cycle performance. The reason is that the surface of the positive electrode material lithium manganese iron phosphate particles of the battery of the embodiment is sequentially coated with SiO 2 Particles, TiO 2 The surface of the positive electrode material lithium manganese iron phosphate particles of the battery in comparative example 2 is only coated with SiO 2 Particles.

[0107] Compared with Comparative Example 3, the battery cycle performance of the embodiment is higher, which is because the surface of the positive electrode material lithium manganese iron phosphate particles of the battery of the embodiment is coated with SiO 2 Particles, TiO 2 The surface of the positive electrode material lithium manganese iron phosphate particles of the battery in comparative example 3 is only coated with TiO 2 Particles.

[0108] Compared with uncoated LiMn 0.5 Fe 0.5 PO 4 Compared with the battery made of LiMn powder, the internal resistance of the battery in the embodiment is smaller, the Mn element is less dissolved, the discharge capacity retention rate and the cycle performance are higher. 0.5 Fe 0.5 PO 4 The powder is coated with SiO 2 and TiO 2 , which can improve the performance of the battery.

[0109] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A positive electrode material, characterized in that: include: It comprises lithium iron manganese phosphate particles and a first shell layer and a second shell layer sequentially coated on the surface of the lithium iron manganese phosphate particles, wherein the material of the first shell layer comprises nano-scale SiO2 particles, and the material of the second shell layer comprises nano-scale TiO2 particles.

2. The positive electrode material according to claim 1, characterized in that The average particle size of the SiO2 particles is ≤8nm; and / or, The average particle size of the TiO2 particles is ≤8nm; and / or, The chemical formula of the lithium iron manganese phosphate particles is LiMn x Fe (1-x) PO4, where 0.1≤X≤0.

9.

3. The positive electrode material according to claim 1, characterized in that In the positive electrode material, the mass percentages of the SiO2 particles, the TiO2 particles and the lithium iron manganese phosphate particles are (0.3%-0.7%): (0.3%-0.7%): (98.6%-99.4%).

4. A method for preparing a positive electrode material, characterized in that: The following steps are involved: Providing nano-scale SiO2 particles, lithium iron manganese phosphate particles and an alcohol solvent, dispersing the SiO2 particles in the alcohol solvent, adding the lithium iron manganese phosphate particles, performing a first heating and stirring, and obtaining first solid particles; Nano-sized TiO2 particles are coated on the surface of the first solid particles to obtain a positive electrode material.

5. The method for preparing the positive electrode material according to claim 4, characterized in that: In the positive electrode material, the mass percentages of the SiO2 particles, the TiO2 particles and the lithium iron manganese phosphate particles are (0.3%-0.7%): (0.3%-0.7%): (98.6%-99.4%); and / or, The temperature of the first heating is 60° C. to 90° C., and the time of the first heating is 4 h to 12 h.

6. The method for preparing the positive electrode material according to claim 4, characterized in that: The step of coating the surface of the first solid particles with nano-sized TiO2 particles comprises: Providing tetra-n-butyl titanate and anhydrous ethanol, dispersing the tetra-n-butyl titanate in the anhydrous ethanol, and mixing the tetra-n-butyl titanate with the first solid particles after dispersion to obtain a suspension; Water is provided and added to the suspension, and a second heating and stirring is performed.

7. The method for preparing the positive electrode material according to claim 6, characterized in that: The temperature of the second heating is 50° C.-70° C., and the time of the second heating is 4 h-8 h.

8. The method for preparing the positive electrode material according to claim 6, characterized in that: The providing of water, added to the suspension, comprises: An aqueous solution of ethanol is provided and added to the suspension.

9. The method for preparing the positive electrode material according to claim 8, characterized in that: The volume ratio of ethanol to water in the ethanol aqueous solution is (1-3):

1.

10. The method for preparing a positive electrode material according to any one of claims 4 to 8, characterized in that: Also includes: After coating the surface of the first solid particles with nano-sized TiO2 particles, sintering is performed to obtain a positive electrode material.

11. The method for preparing the positive electrode material according to claim 9, characterized in that: The sintering temperature is 400° C.-600° C., and the sintering time is 3 h-6 h.

12. A positive electrode sheet, characterized in that: The invention comprises a positive electrode material as described in any one of claims 1 to 3 or a positive electrode material prepared by the method for preparing the positive electrode material as described in any one of claims 4 to 11.

13. A battery, characterized in that: Comprising the positive electrode sheet as described in claim 12.

Citation Information

Patent Citations

  • Lithium-rich cathode material doped with lithium manganate at Mn site, and preparation method of lithium-rich cathode material

    CN107994226A

  • A ternary cathode material coated with double oxides and a preparation method thereof

    CN109037602A

  • Coated modified electrode material and preparation method thereof

    CN109585797A

  • Positive electrode material and preparation method thereof

    CN112968150A

  • Lithium ion battery positive electrode material, positive electrode plate and lithium ion battery

    CN113675381A

Cited By

  • Lithium manganese iron phosphate composite positive electrode material, preparation method thereof and lithium ion battery

    CN120097307A

  • Lithium iron manganese phosphate composite cathode material, preparation method thereof and lithium ion battery

    CN120097307B

  • Flaky composite lithium manganese iron phosphate material and preparation method thereof

    CN121528897A

  • A flaky composite lithium manganese iron phosphate material and a preparation method thereof

    CN121528897B

  • Positive electrode material, preparation method therefor, positive electrode sheet and battery

    EP4779710A1